Variations in renal morphometry: A hospital-based Indian study - Rathore, Ranjeet S. (Indian J Urol, 2016)
INTRODUCTION: The currently available standard renal nomograms for comparison of renal dimensions in India are based on the measurements made in the Western population. The objectives of our study were to identify variations in renal morphometric parameters in subjects with no known renal disease in a hospital-based Indian population and to find out any correlation between renal volumes with split renal functions and body mass index (BMI). MATERIALS AND METHODS: One hundred and fifty-one subjects undergoing contrast-enhanced computerized tomography (CT) scan for various purposes, including donor nephrectomy, from June 2012 to August 2014 were included in the study. The renal and ureteral dimensions were assessed from the contrast-enhanced CT scan images of these patients. RESULTS: The mean length, width, thickness and volume of the left kidney were 11.02 ± 1.13 cm, 5.21 ± 0.75 cm, 4.65 ± 0.84 cm and 138.22 ± 29.81 mL, respectively, and those for the right kidney were 10.86 ± 1.12 cm, 5.13 ± 0.77 cm, 4.73 ± 0.95 cm and 137.54 ± 34.48 mL, respectively. The mean length of the left ureter was 23.51 ± 1.48 cm and that of the right ureter was 23.24 ± 1.93 cm. The mean volume of the kidneys in males and females was also different. The volume of the kidney did not statically correlate with the split glomerular filtration rate ((P = 0.12) and BMI (P = 0.52)). CONCLUSIONS: Our study revealed that there exist differences in various morphometric parameters of the kidney and ureter in different subsets of the Indian population attending our hospital as compared with the standard values quoted in the world literature.